Character Education and Citizenship Education in The Middle of Community - Maelani Pariani Puri (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Education is a conscious and well-planned effort to form an intelligent and well-characterized Indonesian society. Civic education is a place to prepare the younger generation with sufficient provisions in the social life needed in society. The ability to think critically, be responsible, have a democratic attitude and act is one of the supporters in the formation of the nation's character. The writing method in this article uses Literature Review. The condition of Indonesia's young generation is currently in a position that is quite disturbing. The declining enthusiasm for learning that is felt at this time has reached a very worrying point. The younger generation is increasingly showing moral deviations which indicate the younger generation no longer has a good character. Therefore, civic education has an important role in the formation of national character. Character values ​​through civic education in schools are one of the mandatory subjects at every level and path of education, from elementary school to college. The formation of national character through civic education is a must because it can form a young generation that is intelligent, and has noble character so that its existence in social life becomes meaningful and characterized.